Pengaruh Kemandirian dan Konsep Diri terhadap Pemecahan Masalah Matematika Siswa - Syela Priyastutik; Huri Suhendri; Soeparlan Kasyadi (JKPM (Jurnal Kajian Pendidikan Matematika), 2018)
The purpose of this research is to know the: (1) influence of independence and self-concept towards problem-solving mathematics, (2) the influence of independence towards solving math problems, and (3) the influence of the concept up to problem-solving Math. Research methods used in this research is a survey method that involves students JSS in the district of Pasar Rebo, namely: SMP Negeri 184 Jakarta, MTs Country 33 Jakarta, and SMP Negeri Jakarta 103. Sampling technique used is stratified random sampling with the number of samples in the study as many as 100 students. Research instrument in the form of the now independence and self-concept, as well as a test problem-solving mathematics essay. Based on test results with significant level whose hypotheses 5% (? = 0.05) it can be concluded that: (1) there is a concept of independence and influence up to problem-solving of mathematics, (2) there is the influence of independence toward problem-solving math, and (3) There is the influence of the concept of mathematical problem solving themselves against. So, someone who has independence will form a positive self-concept so that it is able to solve the problem.